Diagnosis and management of intraductal papillary mucinous neoplasms of the pancreas - Cortegoso Valdivia, Pablo; Chialà, Claudia; Venezia, Ludovica; Gaiani, Federica; Leandro, Gioacchino; Di Mario, Francesco; de' Angelis, Gian Luigi (Acta Biomedica Atenei Parmensis, 2018)
Background and aim of the work: Intraductal papillary mucinous neoplasms (IPMN) of the pancreas are cystic lesions with malignant potential. Given their increasing incidence in the latest years, a precise characterization and management of these lesions have become more and more crucial: even though the majority of IPMN has a benign and indolent course, it is fundamental to early recognize and stratify patients in order to accurately plan a tailored follow-up and to individuate those that would benefit of surgical treatment. The aim of this paper is to highlight the most recent evidence on IPMN available in the current literature. Methods: We performed a review of the recent literature and of the recent guidelines about pancreatic cystic lesions, especially IPMN. Results: The incidence of IPMN is now on the rise: an increasing number of patients, possibly because of the increasing diagnostic yield of imaging techniques, is being diagnosed with pancreatic cystic lesions, a great part of which are IPMN. The possibility of malignant transformation requires a careful approach to these patients, in the need of tailoring the follow-up and the therapy. Conclusion: A detailed diagnosis, the determination of risk factors for malignant transformation and a multisciplinary approach are of foremost importance for an effective management of IPMN.